METAL-SILICATE PARTITIONING OF CO, GA, AND W: DEPENDENCE ON SILICATE MELT COMPOSITION - Jaeger W.L.; Drake M.J. (My University, 2000)
This study investigates the effect of silicate melt composition on metal/silicate partitioning for Co2+, Ga3+, and W4+ at 1300°C, 1 atm, and a log fO2 of -12. Five glasses in the system MgO-CaO-Al2O3-TiO2-SiO2 with nbo/t (nonbridging oxygens/tetrahedrally coordinated cations) values ranging from 0.25 to 1.52 were used as starting materials. For W and Co experiments the five glasses were equilibrated with W or Co wire loops, respectively, at the specified run conditions. For Ga experiments the glasses were doped with 2 wt.% Ga2O3 and equilibrated with pure Fe. All phases were analyzed by an electron microprobe. The metal/silicate partition coefficient for W depends strongly on melt basicity, whereas the effect of melt composition on Ga partitioning is less pronounced and for Co it is negligible. DW decreases rapidly with increasing nbo/t, DGa decreases moderately with increasing degree of melt basicity, and DCo remains relatively constant over our compositional range. The findings of this study indicate that the effect of melt composition on trace element solubility is a function of cation oxidation state such that high valency cations like W4+ are more readily dissolved in depolymerized melts which have a higher ratio of nonbridging oxygens, and lower valency cations like Co2+ are relatively independent of the parameter nbo/t. These results confirm that the composition of the primitive mantle is an important factor in constraining how siderophile trace elements distribute themselves between an Fe-metal core and the bulk silicate Earth during an early magma ocean differentiation event.